Clinical spectrum, complications and management outcomes in paediatric dengue: a retrospective analysis - Abhishek S. Parlikar; Puja R. Totala; Rashmi S. Sherodkar; Amit S. Pilkhane; Rajkumar R. Narwade (International Journal of Contemporary Pediatrics, 2026)
Background: The dengue fever remains a major cause of acute febrile illness among children in India. To provide region-specific data from central Maharashtra, this study evaluated the clinical spectrum, complications, outcomes and impact of steroid therapy in paediatric dengue patients. Methods: This retrospective observational study was conducted at a tertiary care centre in Chhatrapati Sambhajinagar, Maharashtra covering the period of January 2021 to December 2025. A total of 355 children (